Transitivity Analysis of The Main Character in Front Desk: Linguistic Portraits of Racial Dynamics in Young Adult Fiction - Nirwana; Mustafa, Mutakhirani; Muhlis (Metathesis: Journal of English Language, Literature, and Teaching, 2024)
This article applies Systemic Functional Linguistics (SFL) to conduct a transitivity study of racial prejudice depiction in Kelly Yang's young adult fiction novel "Front Desk." The study dives into the linguistic representation of racial dynamics utilizing SFL's transitivity paradigm, focusing on the experiences of Mia, the main character of the novel dealing with racial prejudice in the United States. Beginning with a review of relevant literature on racial bias in literary works, the study offers a conceptual framework, stressing dominant groups' property claims. The analysis deconstructs Mia's experiences through material, verbal, relational, mental, and behavioral processes, exposing how linguistic choices generate systemic hurdles and social biases. The findings highlight Mia's frequent physical actions, emotional responses to racial discrimination, and extensive verbal communication, all of which demonstrate the pervasiveness of systemic hurdles in her life. The study contrasts Mia's experiences with characters from other literary works to interpret racial relations. The study examines the language of race in "Front Desk," emphasizing the novel's dual importance in showing immigrant problems and promoting critical observations on racial concerns. The conclusion states that the novel's linguistic portrayals play a critical role in influencing readers' understanding of racial dynamics, emphasizing language's ability not just to reflect but also to question existing conventions.